A critical review of Malaysia’s accomplishment on water resources management under AGENDA 21 - Chan, Ngai Weng (Environmental Management Society, Malaysia, 2004)
Malaysia is a signatory of the Rio Summit in 1992 and is bound by agreement to satisfy all the requirements of country-wise sustainable management of water resources. While many steps have been taken there is still much to do before Malaysia completely satisfies all the Agenda 21 requirements under Chapter 18. There is the absence of a clear-cut National Water Resources Policy to guide the sustainable development of water resources and water sector strategies. While laws for the protection and conservation of water resources are adequate, poor enforcement is a major problem. Malaysia has also not explored the development of new and alternative sources of water-supply but continue to rely on rivers which are increasingly polluted. Public participation in water resources management is poor, largely due to reluctance of the water authorities to use the public and also public apathy. Decision-making in water resources planning and management is still largely a Top-Down approach. Rapid unplanned urban development that decimated forests have led to flooding. Finally, climate change such as El Nino and La Nina is another major problem. Privatisation of the water industry has not been as successful as it ought to be, mostly due to the lack of meritocracy, transparency, accountability and expertise